Konsep Pendidikan Akhlak Perspektif Imam ‘Abdullah bin Alwi Al-Haddȃd dalam Kitab An-Nashȃih Ad-Dîniyyah Wa Al-Washȃyȃ Al- Îmȃniyyah - Siti Rohmah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2020)
This Study, the writer raises the moral issues that occur in this Globalization Era with the concept of moral education according to Imam 'Abdullah bin Alwi al-Haddȃ in his book an-Nashȃih ad-Dîniyyah Wa al-Washȃyȃ al-Îmȃniyyah. The purpose of this research is to find out the concept of moral education in the perspective of Imam 'Abdullah bin Alwi al-Haddȃ in his book an-Nashȃih ad-Dîniyyah Wa al-Washȃyȃ al-Îmȃniyyah. In this study, the authors used this type of library research or library research with a qualitative approach. Data collection techniques with documentation and data analysis techniques using a Content Analysis approach (content analysis or study). The results showed that the concept of moral education in the perspective of Imam 'Abdullah bin Alwi al-Haddȃ consists of 2 aspects, namely; first, moral education to Allah, which includes obedience to Allah; repentance, patience, sincerity, adab reading the Al-Qur'an, the adab of praying and the adab of fasting, while obedience keeps away from all His prohibitions including; stay away from adultery, stay away from liquor (khamar). Second, moral education for humans, including; be kind to both parents, be kind to neighbors, and be kind to friends. The moral education contained in the book an-Nashaid ad-Diniyah is in the form of orders, recommendations and prohibitions. Imam Abdullah's concept of moral education is very relevant to today's moral education which is very much needed in the era of globalization, which is based on its benchmarks derived from Al -Qur'an and hadith.